Crypto Connections: Unravelling African Stock Markets and Cryptocurrencies in the COVID-19 Era - Marcus, Howard (University of the Witwatersrand, Johannesburg, 2024)
Since their introduction in 2019, cryptocurrencies have become increasingly popular in the African markets. Cryptocurrencies are seen as disruptive technology based on cryptographical technologies and do not share features related to the real economy. Based on this characteristic, one hypothesises that these assets are a perfect diversification instrument during periods of high volatility, particularly as portfolio managers look for new avenues to manage risk. The main aim of this study was broadly focused on the interdependence and co-movement relationship of cryptocurrencies and African stock markets during periods of severe market stress, such as during the COVID-19 pandemic. This study was mainly concerned with those aspects of connectedness that relate to transmission through financial markets. This study sought to examine the co-movement relationships, determine the extent of integration and establish the direction of spillover by replicating modelling techniques proposed by Diebold and Yilmaz (2009; 2012) and Barunik and Krehlik (2018). These techniques measure connectedness using a spillover index, which follows a variance decomposition approach of a vector autoregressive model. The second technique allows for the estimation of connectedness to variables because of heterogeneous frequency responses to shocks. By studying the connectedness of Bitcoin, Ethereum, Tether, Binance Coin, and XRP and the five largest African stock markets based on market capitalisation (South Africa, Nigeria, Morocco, Egypt, and Kenya), the study observed that the COVID-19 sub-sample period contributed most to connectedness at 31.79% relative to the pre-COVID period at 23.67%. The highest contributors to connectedness in both periods are Bitcoin and Ethereum, with Tether being the lowest. These results indicate that information flow mostly comes from the stock markets rather than cryptocurrencies. Also, from the frequency-domain results, across both periods, the most significant contributor to connectedness is observed in the short-term being frequency 1, accounting for 17,74% and 24.77%, and frequency 2, 4.35% and 5.16% in the pre-COVID and COVID periods respectively, while the medium- term and long-term accounting for relatively more minor proportions. Thus, contagion is highest in the short term given connectedness results, thus leading to lower diversification across the short term; however, diversification benefits are noted across more extended term periods. In addition, in the longer-term period, the change in connectedness is relatively tiny. The findings of this study suggest that cryptocurrencies could be an alternative to diversifying risk in African equities. Diversification is essential for long-term investors and regulators as they build resilience in the financial markets during a crisis. This study informs policymakers and governments on the need to regulate markets to optimise diversification, safe haven, and hedging benefits across varied market conditions
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Finance and Investments to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: African Stock Market; Connectedness; Contagion; Cryptocurrency; COVID-19; Frequency-domain; Time-domain; UCTD; SDG-8: Decent work and economic growth